Suppressing T cell motility induced by anti-CTLA-4 monotherapy improves antitumor effects. - Ruocco, MG; Pilones, K; Kawashima, N; Cammer, M; Huang, J; Babb, J; Liu, M; Formenti, S; Dustin, M; Demaria, S (2012)
A promising strategy for cancer immunotherapy is to disrupt key pathways regulating immune tolerance, such as cytotoxic T lymphocyte-associated protein 4 (CTLA-4). However, the determinants of response to anti-CTLA-4 mAb treatment remain incompletely understood. In murine models, anti-CTLA-4 mAbs alone fail to induce effective immune responses to poorly immunogenic tumors but are successful when combined with additional interventions, including local ionizing radiation (IR) therapy. We employed an established model based on control of a mouse carcinoma cell line to study endogenous tumor-infiltrating CD8+ T lymphocytes (TILs) following treatment with the anti-CTLA-4 mAb 9H10. Alone, 9H10 monotherapy reversed the arrest of TILs with carcinoma cells in vivo. In contrast, the combination of 9H10 and IR restored MHC class I-dependent arrest. After implantation, the carcinoma cells had reduced expression of retinoic acid early inducible-1 (RAE-1), a ligand for natural killer cell group 2D (NKG2D) receptor. We found that RAE-1 expression was induced by IR in vivo and that anti-NKG2D mAb blocked the TIL arrest induced by IR/9H10 combination therapy. These results demonstrate that anti-CTLA-4 mAb therapy induces motility of TIL and that NKG2D ligation offsets this effect to enhance TILs arrest and antitumor activity.